Analisis Hukum Dampak Praktik Penggandaan Buku Terhadap Hak Ekonomi (Royalti) Pencipta - Alfian Septawibisono; Ranggalawe Suryasaladin (LPPM Universitas Ekasakti Padang, 2023)
In this study, the authors raised the issue of Royalty Protection for the Practice of Copying Books. The choice of the theme was motivated by the fact that book copying in Indonesia is increasingly being carried out by several parties, such as photocopying service providers and digital platforms or marketplaces that sell fake books from the original copies. Copyright infringement carried out with this photocopy machine has violated the exclusive rights of the creator, especially economic rights. As the protection of the author of a book is very important whose aim is that the author can feel appreciation for the work that has been made by using his creative thoughts and ideas in the form of royalties for the use of the license that the author has given to other parties. Based on Law No. 28 of 2014 concerning Copyright, the Reproduction of books for commercial purposes and without prior permission to the creator or copyright holder is very clearly referred to as a violation, because it violates the economic rights of the creator where copying books for commercial purposes is carried out only for business and profit purposes and the creator does not get royalties for the violation